Enhancement of humidity sensitivity of graphene through functionalization with polyethylenimine - Ben Aziza, Zeineb (2015)
In this work, we show that the sensing performance of graphene based humidity sensors can be largely improved through polymer functionalization. Chemical vapor deposited graphene is functionalized with amine rich polymer, leading to electron transfer from amine groups in the polymer to graphene. The functionalized graphene humidity sensor has demonstrated good sensitivity, recovery, and repeatability. Charge transfer between the functionalized graphene and water molecules and the sensing mechanism are studied systemically using field effect transistor geometry and scanning Kelvin probe microscopy.